(untitled) (University of Khartoum Engineering Journal, 2021)
The Zone and Energy Aware protocol based on the Ad hoc On demand Distance Vector (AODV) protocol (ZEA-AODV) provides a superior performance compared to the classic AODV protocol when number of nodes is less than 70 [1]. ZEA-AODV protocol is using location and energy information to reduce energy consumption and routing overhead. It is a combination of the two proposed protocols, Zone-aware AODV (Z-AODV) protocol and Energy-Balanced AODV (EB-AODV) protocol. In [1], we assumed that each host knows its current location precisely. In this paper, Global Positioning System (GPS) error is considered, therefore, the standard GPS error is modelled by generating two samples for movement of a terminal by simulation. One of the movements is as a simulation of the actual movement, and the other one as a simulation of the error. Then both movements are provided to the terminal. This GPS error modelling is considered in the case of ZEA-AODV protocol to investigate the effect of such error on its performance. Using the simulation, it is found that, although the overall performance of ZEA-AODV protocol is degraded when GPS error is considered, but energy conservation is noticeably still better than that of normal AODV protocol.